Diagnosis of earth-fill dams by synthesised approach of sounding and surface wave method. Issue 4 (1st October 2016) - Nishimura, Shin-ichi; Shibata, Toshifumi; Shuku, Takayuki
ABSTRACT: The spatial distribution of the strength inside the earth-fill is identified by the sounding tests. In this research, the Swedish weight sounding (SWS) is employed, and the spatial high-density test is performed to identify the spatial correlation structure. Furthermore, the synthesised approach of the SWS and surface wave method, which is one of the geophysical method, is proposed to compensate the shortage of each approach. Consequently, the correlation structure of an earth-fill could be identified accurately, and the high resolution of the spatial distribution could be visualised based on the survey results.